Gestão de pressões institucionais em cooperativas: estudo comparativo entre Brasil e Austrália - Simão, Gustavo Leonardo (2018)
Dairy cooperatives are faced with different institutional demands to legitimize themselves in their organizational field. Under this context, organizational actors are subject to an institutional perspectives scenario with ambivalent demands. The present work attempted, using a multi-level study, to analyze how dairy cooperatives, considering different organizational structures, in Brazil, specifically in Minas Gerais state, and Australia, response to two apparently ambivalent institutional orders (subfields). Qualitative data were obtained by semi-structured interviews and documentary research in six cooperatives located in Brazil and two in Australia. The results, besides pointing out the structural peculiarities in each case, also report the main problems in the context of these organizations. In relation to institutional responses, it is inferred that in the Brazilian case there is a decoupling where the legitimation actions are apparently put in balance, when in fact they are predominantly based only to meet institutional demands related to agribusiness (non- cooperative) order. In Australian case, strong legal and market demands put cooperative actors constrained to consider the priority cooperative Act enforcement, in addition to non-cooperative market demands, which leads to balanced response.